Exchange Rates in Central Europe : A Blessing or a Curse? - Kuijs, Louis (IMF Working Papers; Working Paper ;, 2004)
Central European accession countries (CECs) are currently considering when to adopt the euro. From the perspective of macroeconomic stabilization, the cost or benefit of giving up a flexible exchange rate depends on the types of asymmetric shocks hitting the economy and the ability of the exchange rate to act as a shock absorber. Economic theory suggests that flexible exchange rates are useful in absorbing asymmetric real shocks but unhelpful in the case of monetary and financial shocks. For five CECs-the Czech Republic, Hungary, Poland, the Slovak Republic, and Slovenia-empirical results on the basis of a structural VAR suggest that in the CECs the exchange rate appears to have served as much or more as an unhelpful propagator of monetary and financial shocks than as a useful absorber of real shocks.